2020
DOI: 10.1177/0961000620919783
|View full text |Cite
|
Sign up to set email alerts
|

Theory of planned behaviour factors and personality traits as determinants of the knowledge-sharing behaviour of pharmacists in Oyo State, Nigeria

Abstract: While many studies have attempted to understand knowledge-sharing practices in the health-care industry, there is a dearth of knowledge about the determinants of the knowledge-sharing behaviour of pharmacists. The present study employed theory of planned behaviour constructs and personality traits to assess factors affecting the knowledge-sharing behaviour of pharmacists in Oyo State, Nigeria. A descriptive survey research design was adopted, with the use of a structured questionnaire as the data collection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The founder of TPB, Ajzen (1991), clearly explained that only positive intention will lead to actual behavior. Congruent with Ajzen (1991), Opesade and Alade (2020) find that people tend to share knowledge when there is a positive intention, whereas Al-Kurdi et al (2020) report that positive intentions predict KSB among UK academics. Taken collectively, we anticipate that:…”
Section: The Structural Relationships Between Theory Of Planned Behav...mentioning
confidence: 99%
See 2 more Smart Citations
“…The founder of TPB, Ajzen (1991), clearly explained that only positive intention will lead to actual behavior. Congruent with Ajzen (1991), Opesade and Alade (2020) find that people tend to share knowledge when there is a positive intention, whereas Al-Kurdi et al (2020) report that positive intentions predict KSB among UK academics. Taken collectively, we anticipate that:…”
Section: The Structural Relationships Between Theory Of Planned Behav...mentioning
confidence: 99%
“…While some scholars have used guiding theories such as social capital theory (Fauzi et al, 2019), social exchange theory (Yan et al, 2016) and theory of reasoned action (Ng, 2020), other scholars have relied only on a part of the theory (e.g. TPB without actual behavior and/or salient beliefs; Al- Fauzi et al, 2018;Al-Kurdi et al, 2020;Opesade and Alade, 2020). The founder of TPB, Ajzen (1991), suggested that the use of the full version of TPB, which includes three different kinds of salient beliefs.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kim and Oh (2021) integrated TPB, community considerations, and reciprocity to examine social and individual motivation factors affecting researchers’ article-sharing intentions. Opesade and Alade (2021) employed TPB constructs and personality traits to assess factors affecting the knowledge-sharing behavior of pharmacists in Oyo State, Nigeria. Sharma et al (2021) developed a conceptual framework incorporating the Social Identity Theory, SET and TPB to investigate factors that impact gamers’ gifting behavior in online games.…”
Section: Theoretical Frameworkmentioning
confidence: 99%